Sorting Out Disasters: A New Case Study for Classification Theory - Braun, Daniel (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2006)
Abstract: In Sorting Things Out: Classification and its Consequences, Geoffrey Bowker and Susan Star present a model of classification in which informal classification practices, performed by people through their everyday, ad-hoc decision-making, necessarily subvert the formal classification schemes, characterized as systemic and bureaucratic, within which they are performed. While this model affords significant theoretical purchase on classification practices, this paper show that a more nuanced relationship exists between formal and informal classification. The practices through which Canadian government officials evaluate and respond to requests for financial aid in the wake of disasters provide instances of classification in which informal classification reinforces, rather than subverts, formal classification.